Microwave-assisted synthesis and characterization of BiOIO3 nanoplates for photocatalysis - Patiphatpanya P. (2017)
© 2017 Elsevier B.V. New polar BiOIO 3 nanostructures were successfully synthesized by 90 and 180 W microwave for 20–100 min. X-ray diffraction (XRD), transmission electron microscopy (TEM) and UV–visible spectroscopy revealed the presence of pure orthorhombic BiOIO 3 nanoplates with 2.5–2.9 eV energy gap. The photodegradation of rhodamine B (RhB) by BiOIO 3 photocatalyst was tested under visible radiation for 60 min. In this research, BiOIO 3 photocatalyst synthesized by 180 W microwave for 60 min has the highest activity of 96%.